2018
DOI: 10.1007/s00264-018-4031-7
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue micro-circulation in the healthy hindfoot: a cross-sectional study with focus on lateral surgical approaches to the calcaneus

Abstract: In non-trauma situations, young males were associated with better micro-circulatory supply of the lateral hindfoot. There was a trend for higher blood flow in regions of the Palmer and Ollier approach. The distal calcaneal tuberosity was clearly superior in all micro-circulatory parameters when compared to the surrounding area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…Another limitation is that functional outcomes of those cases with peroneal tendon dislocation were not uniformly recorded, which precludes comparison to those with talus fractures with no concurrent peroneal tendon dislocation. However, morbidity associated with isolated peroneal tendon dislocation has been described in literature and touched upon earlier in this discussion [17][18][19].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another limitation is that functional outcomes of those cases with peroneal tendon dislocation were not uniformly recorded, which precludes comparison to those with talus fractures with no concurrent peroneal tendon dislocation. However, morbidity associated with isolated peroneal tendon dislocation has been described in literature and touched upon earlier in this discussion [17][18][19].…”
Section: Discussionmentioning
confidence: 94%
“…Chronic dislocation is associated with tear of the peroneus brevis due to attrition against the posterolateral ridge of the fibula. This adds to the morbidity of talus fractures and may lead to inferior outcomes of surgical treatment (17)(18)(19). Another implication of the presence of peroneal tendon dislocation is that it may affect approach selection for open reduction and internal fixation to allow for examination and treatment of the peroneal dislocation while maintaining maximum exposure.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, gender differences in microcirculation in relation to hip surgery have not been previously reported. In a study on microcirculation in the hindfoot with healthy subjects, higher values were registered for men than women (Carow et al, 2018). Reasons might include more subcutaneous fat tissue in women compared to men (Carow et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, differences in microcirculation were found between surgical approaches in spine surgery, i.e., less impairment of microcirculation in minimally invasive surgery of the spine compared to open surgery (Ganse et al, 2017). Distinctions in microcirculation between approaches in Achilles tendon surgery in healthy subjects (Klos et al, 2018), gender differences in skin microcirculation over the calcaneus (Carow et al, 2018) and effects of pulsed ultrasound therapy in the foot were published (Kösters et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gentle handling of soft tissue during raising of the lateral skin flaps to ensure good circulation is the most important factor in our opinion [18] [19]. Blade size 15 was used to make a curvilinear incision straight down to bone.…”
Section: Discussionmentioning
confidence: 99%